ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENERIMAAN DAN PENGGUNAAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) DENGAN MENGGUNAKAN MODEL UTAUT 2 (Studi Empiris pada Pengguna Sistem informasi Manajemen Daerah (SIMDA) di Kota Salatiga) - Anggita Setyorini; Wahyu Meiranto (Diponegoro Journal of Accounting, 2021)
This study aims to analyze the factors that influence the acceptance and use of the Regional Management Information System (SIMDA) by applying the model proposed by Venkatesh et al. (2012) namely The Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2). There are eight factors that form the basis of measurement in this study, namely performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, habit, behavioral intention, and use behavior of SIMDA.In this study, all SIMDA users or operators at all OPD in Salatiga City were used as the population. The survey method with questionnaires distributed directly was applied to obtain data research. 100 questionnaires from the total of 132 back questionnaires were processed as sample and analyzed using PLS (Partial Least Square) method with a data processing application program, namely SmartPLS version 3.The results showed that of the nine hypotheses in this study, only four hypotheses were accepted. Performance expectancy, effort expectancy, social influence, and facilitating conditions have no influence on the behavioral intention to use SIMDA. The facilitating condition variable was also stated to have no influence on the use behavior of SIMDA. While the variables that affect the behavioral intention to use SIMDA are only hedonic motivation and habit. The variables of habit and behavioral intention to use are proven to have an effect on use behavior of SIMDA.